Understanding and Influencing Perceptions about Marine Protected Areas Through an Aquarium Exhibit: A Multi-phase Case Study from South Africa. Issue 1 (April 2023) - Mann-Lang, Judy B.; Naidoo, Thashnee; Francolini, Elizabeth; Mann, Bruce Q; Sink, Kerry; Bodenstaff, Colette
Visitors to Marine Protected Areas (MPAs) provide income and can help MPAs achieve their objectives, thereby contributing to the maintenance and restoration of ocean health. However, MPAs are less well known than terrestrial protected areas. Based at the uShaka Sea World aquarium in South Africa, this multi-phase case study sought to describe visitors' knowledge of MPAs; use the information to design a new temporary interpretive exhibit on MPAs and then use timing and tracking to assess visitors' engagement with the exhibit and a free response postcard system to assess the influence of the exhibit on visitors' perceptions of MPAs. Initial survey results showed that visitors had little knowledge of MPAs. Assessment after installation revealed some surprising levels of engagement and the free response postcards showed positive perceptions and a deeper understanding of MPAs. The results provide recommendations to enhance communication and engagement strategies both in aquariums and MPAs.